Hydrate dissociation condition measurement of CO2-rich mixed gas in the presence of methanol/ethylene glycol and mixed methanol/ethylene glycol + electrolyte aqueous solution - Nasir, Q. (American Chemical Society, 2014)
In this work, the hydrate dissociation condition for carbon dioxide rich gas mixture in the presence of methanol, methanol + sodium chloride or calcium chloride, and ethylene glycol, ethylene glycol + sodium chloride or calcium chloride aqueous solution, were measured and reported. The measurements are carried out at temperature and pressure range of (263.85 to 284.75) K and (2.76 to 12.08) MPa. All data were measured using the isochoric pressure search method. In order to exhibit the inhibition effect of above-mentioned aqueous solution, a comparison was made between experimental data of carbon dioxide rich gas mixture in the presence of pure water and aqueous solutions consist of inhibitor and electrolytes. Furthermore, a thermodynamic model was used to correlate the experimental values. Â© 2014 American Chemical Society.